2016
DOI: 10.1007/978-3-319-46547-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Semantic Information for e-Commerce

Abstract: Rakuten Ichiba uses a taxonomy to organize the items it sells. Currently, the taxonomy classes that are relevant in terms of profit generation and difficulty of exploration are being manually extended with data properties deemed helpful to create pages that improve the user search experience and ultimately the conversion rate. In this paper we present a scalable approach that aims to automate this process, automatically selecting the relevant and semantically homogenous subtrees in the taxonomy, extracting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Data semantics is not just to reveal the actual content of the message but also to determine the framework of words used in the subject matter. It is found that adding suitable semantic and syntactic classification systems to the questions significantly improved question classification efficiency [10,38]. The researchers used various information sources to calculate "semantic-relatedness" between words [38].…”
Section: Semantic Importance In Information Retrievalmentioning
confidence: 99%
“…Data semantics is not just to reveal the actual content of the message but also to determine the framework of words used in the subject matter. It is found that adding suitable semantic and syntactic classification systems to the questions significantly improved question classification efficiency [10,38]. The researchers used various information sources to calculate "semantic-relatedness" between words [38].…”
Section: Semantic Importance In Information Retrievalmentioning
confidence: 99%
“…Since access points are typically based on materialised special purpose database views, to make a new view or to modify an existing one, IT staff typically use external tools, such as Feature Manipulation Engine (FME). 5 The process of making such view consists of the three ETL steps (extracting, transforming, and loading data) Building such ETL processes that establishes an access point for a complex information need consists of a myriad of data access and processing steps, many of which require deep knowledge of the data that is being processed and how it is represented. Figure 2 shows an excerpt of an FME process that establishes an access point for gathering the information for the information need about overlapping core samples that we took from Equinor and anonymised.…”
Section: Finding Data Is As Hard As Finding Oilmentioning
confidence: 99%
“…In the last decade a number of standardised machine processable ontology languages have been developed, where the most popular are W3C standardised RDF (w3.org/RDF/), OWL 2 (w3.org/TR/owl2-overview/). Ontologies have been successfully used in many applications, including Web search [3], Medicine [4], E-commerce [5], Media [6], etc.…”
Section: Introductionmentioning
confidence: 99%
“…e NERC system will have a lot of di culty in using such non-atomic products. Work has also been done on ontologies that are focused more on the catalog side [2,15]. Catalog-side ontologies are closer to searchside ontologies as compared to supply-side ontologies but are still not perfectly aligned with a search perspective.…”
Section: Ontologymentioning
confidence: 99%